Decreasing Defoliation Frequency Enhances Bromus valdivianus Phil. Growth under Low Soil Water Levels and Interspecific Competition - Javier García-Favre; Yongmei Zhang; Ignacio F. López; Daniel J. Donaghy; Lydia M. Cranston; Peter D. Kemp (Agronomy, 2021)
Bromus valdivianus Phil. (Bv) is a water stress-tolerant species, but its competitiveness in a diverse pasture may depend on defoliation management and soil moisture levels. This glasshouse study examined the effect of three defoliation frequencies, based on accumulated growing degree days (AGDD) (250, 500, and 1000 AGDD), and two soil water levels (80–85% of field capacity (FC) and 20–25% FC) on Bv growth as monoculture and as a mixture with Lolium perenne L. (Lp). The treatments were applied in a completely randomised block design with four blocks. The above-ground biomass of Bv was lower in the mixture than in the monoculture (p ≤ 0.001). The Bv plants in the mixture defoliated more infrequently (1000 AGDD) showed an increase in root biomass under 20–25% FC compared to 80–85% FC, with no differences measured between soil water levels in the monoculture. Total root length was highest in the mixture with the combination of infrequent defoliation and 20–25% FC. Conversely, frequent defoliation treatments resulted in reduced water-soluble carbohydrate reserves in the tiller bases of plants (p ≤ 0.001), as they allocated assimilates mainly to foliage growth. These results provide evidence that B. valdivianus can increase its competitiveness relative to Lp through the enhancement of the root growth and the energy reserve in the tiller base under drought conditions and infrequent defoliation in a mixture.